Risk’s Relations: Dangerous Offender Decisions, Risk Assessment Tools, and State Accountability for Colonial Oppression - Nussbaum, Sarah-jane (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
Sentencing law reveals a tension between judges acknowledging connections between colonialism, criminalization, and imprisonment and using individual sanctions, alone, to address what they identify as the social and institutional dimensions of conflict and harm. This article illuminates the limits of individualized sentencing as a response to colonial oppression by looking closely at judicial engagement with risk assessment tools in the context of “dangerous offender” proceedings. Judges are making progress by holding the state accountable for ensuring that risk assessment tools accurately predict an Indigenous offender’s likelihood of being charged or convicted in the future and for implementing programs in prisons that provide Indigenous offenders with opportunities to change their risk scores. Judges are also acknowledging a well-established critique of these tools—the fact that they measure people’s experiences of oppression for which the state ultimately bears at least some accountability. Unfortunately, even when judges acknowledge that risk is at least partially constructed and maintained by relations of power, there is no concrete outcome available to address such an acknowledgment. The dangerous offender regime requires judges to prioritize public protection through individual sanctions, alone. This analysis leads the author to suggest that some form of authority for sentencing judges to directly assess state accountability for conflict, harm, and their prevention might give rise to decisions that more clearly and fittingly identify how safety can be facilitated by not only individuals but also the state.